0
$\begingroup$

I am practicing for my exam that I have this semester and I stumbled upon this one. How can i find inverse Fourier transform given: $$ X(j\omega) = \sum_{k=-\infty}^{\infty}\delta(\omega-2k+1) $$

$\endgroup$
1
  • $\begingroup$ Have you tried using the definition of the (inverse) FT and the definition of the delta distribution? It's quite straight forward, really. $\endgroup$
    – Jazzmaniac
    Feb 6, 2021 at 19:35

1 Answer 1

1
$\begingroup$

Using Duality Property, we have $X(j\omega) = \delta(\omega-\omega_{0})$. By using this and rewriting our function using $1-2k = -\omega_{0}$, we get: $$\begin{align} x(t) &= \frac{1}{2\pi}\int_{-\infty}^{\infty}\delta(\omega-\omega_{0})e^{j\omega t}d\omega \\ &= \frac{1}{2\pi}e^{j \omega_0 t} \end{align}$$ $$ \sum_{k=-\infty}^{\infty}\delta(\omega-\omega_{k})\leftrightarrow \frac{1}{2\pi}\sum_{k=-\infty}^{\infty}e^{j\omega_{k}t} $$ Hence: $$ \sum_{k=-\infty}^{\infty}\delta(\omega+1-2k)\leftrightarrow \frac{1}{2\pi}\sum_{k=-\infty}^{\infty}e^{j(2k-1)t} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.